Sports architecture - Li Chunmei (Hong Kong : Design Media Publishing Limited, 2010)
This book includes a total of 47 excellent sports buildings which are designed by famous architects around the world. Through the high quality images, detailed drawings and beautiful words, the book fully expresses all aspects of the sports building designs. With rich contents and clear ideas, the book will be a good reference to all readers.
Keywords: Sports facilities -- Design and construction -- Pictorial works; Stadiums -- Design and construction -- Pictorial works